The Application of Interactive Multimedia to Improve Student’s Learning Outcome in Property Appraisal Training - Moh. Ilham Santoso; Akhmad Arif Musadad; Herry Widyastono (Yayasan Keluarga Guru Mandiri, 2024)
Students in The Property Appraisal Training at Financial Education and Training Agency, based on survey results, state that learning using e-books is less effective in improving learning outcomes. The study aims to evaluate the impact of multimedia interaction on the learning outcomes of property appraisal training students. The research used the research and development (RD) that adopts the ADDIE model. Data collection was carried out through tests and questionnaires with a total of two subject matter experts, two media experts, and 28 students. Data analysis used quantitative and qualitative methods. The results of the subject matter expert assessment indicate that multimedia is suitable for use, with a rating of 91.67%. The results of the media expert assessment show that multimedia is suitable for use with a rating of 90%. Field test results show a significant positive correlation between the average learning outcomes before and after using interactive multimedia. The effectiveness test results show an N-gain value of 61%. Given the impact of multimedia-based education on learning outcomes, this approach can be used to teach other subjects and train students. This research can also be used as a basis for exploring the development of interactive multimedia learning for other subjects.